2017
DOI: 10.1111/sms.12889
|View full text |Cite
|
Sign up to set email alerts
|

The development of the physical fitness construct across childhood

Abstract: The measurement of physical fitness (PF) is an important factor from many different perspectives. PF is a determinant of healthy child development as it is related to several health outcomes. However, existing taxonomies of the construct and frequently used fitness assessments vary concerning their theoretical assumptions and practical implications. From a theoretical perspective, the construct of physical fitness covers a variety of motor domains, such as cardiovascular endurance, strength, coordination, or f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 21 publications
3
47
0
1
Order By: Relevance
“…For instance, Utesch et al found a one‐dimensional construct in children aged 9‐11 years using the German Motor Ability Test 6‐18, which consists of eight items (Deutscher Motorik‐Test 6‐18, DMT). Another study of Utesch et al showed a single latent trait in children aged 6‐9 years, using the same test battery. In contrast to the aforementioned studies, the present research used a large item set (ie, 14 items) in order to evaluate the general motor ability hypothesis more adequately.…”
Section: Discussionmentioning
confidence: 91%
“…For instance, Utesch et al found a one‐dimensional construct in children aged 9‐11 years using the German Motor Ability Test 6‐18, which consists of eight items (Deutscher Motorik‐Test 6‐18, DMT). Another study of Utesch et al showed a single latent trait in children aged 6‐9 years, using the same test battery. In contrast to the aforementioned studies, the present research used a large item set (ie, 14 items) in order to evaluate the general motor ability hypothesis more adequately.…”
Section: Discussionmentioning
confidence: 91%
“…According to the work by Utesch et al, we understand the term physical fitness as a motor competence presuming a one‐dimensional structure, which is defined as the ability to successfully complete a number of wide‐ranging motor skills. Physical fitness was tested using the German motor performance test DMT 6‐18, a standardized test battery consisting of eight items testing different subdomains of physical fitness: 20‐m sprint (sprint velocity), balancing backwards on three 3‐m‐long beams with different width (coordination in a task requiring precision), jumping sideward over a middle line for 15 seconds (coordination under time pressure), stand‐and‐reach (flexibility), push‐ups in a period of 40 seconds (strength endurance), sit ups in a period of 40 seconds (strength endurance), standing long jump (power), and 6‐minute run (endurance).…”
Section: Methodsmentioning
confidence: 99%
“…As Kaiser‐Jovy et al did not find a significant influence of hours of media use on sport activity, they concluded that a heavy media use is part of a complex juvenile leisure behavior and therefore rather a “time killer” with regard to sport activity and physical fitness. In general, physical fitness is subdivided into health‐related fitness (cardiorespiratory endurance, muscular endurance and strength, body composition, flexibility) and skill‐related fitness components (agility, balance, coordination, speed, power, reaction time) which can be tested by a single test item assessment (eg, “shuttle run” covering cardiovascular endurance) or by entire motor test batteries . There is evidence that a decrease in physical fitness is associated with an increase in body mass index among children and adolescents .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations